Transplantation of infant kidneys - the surgical technique en bloc and transplant position variation: A case report - Popović Vladan; Sekulić Vuk; Manojlović Vladimir; Milošević Đorđe; Nikolić Dragan; Pasternak Janko (Vojnosanitetski Pregled)
Introduction. Due to the ever-present lack of kidney transplant grafts, more and more organs obtained from the so-called “marginal donors” group are accepted, which can provide suboptimal effect of transplantation, depending on their characteristics and/or implantation techniques. Case report. We presented a case with successful variation of kidney position with modified approach of kidney transplantation from an infant to an adult female patient with normal postoperative recovery. Urethral anastomosis was performed without antireflux procedure and this has not led to the development of reflux disease at an early stage. Conclusion. The position of a pair of kidneys proved to be satisfactory despite the growth of the kidney to the expected size and relatively small pelvis. There were no problems with venous stasis and kidney function from the very beginning was good.